2021
DOI: 10.3390/antibiotics10020124
|View full text |Cite
|
Sign up to set email alerts
|

Phage-Encoded Endolysins

Abstract: Due to the global emergence of antibiotic resistance, there has been an increase in research surrounding endolysins as an alternative therapeutic. Endolysins are phage-encoded enzymes, utilized by mature phage virions to hydrolyze the cell wall from within. There is significant evidence that proves the ability of endolysins to degrade the peptidoglycan externally without the assistance of phage. Thus, their incorporation in therapeutic strategies has opened new options for therapeutic application against bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
130
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 177 publications
(178 reference statements)
0
130
0
1
Order By: Relevance
“…Numerous endolysin studies confirm the in vitro effectiveness of these enzymes and describe valuable advantages of their use to combat multiple Gram-positive or -negative bacterial pathogens. However, very few of the studies are devoted to in vivo application and just several molecules are in clinical trials ( Abdelrahman et al, 2021 ; Grabowski et al, 2021 ; Schmelcher and Loessner, 2021 ). Such a trend does not promote the acceleration of the development and implication of endolysin-based drugs into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous endolysin studies confirm the in vitro effectiveness of these enzymes and describe valuable advantages of their use to combat multiple Gram-positive or -negative bacterial pathogens. However, very few of the studies are devoted to in vivo application and just several molecules are in clinical trials ( Abdelrahman et al, 2021 ; Grabowski et al, 2021 ; Schmelcher and Loessner, 2021 ). Such a trend does not promote the acceleration of the development and implication of endolysin-based drugs into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to whole-phage preparations, isolated natural and genetically engineered enzymes of Proteus phages (endolysins, polysaccharide depolymerases) have not been intensively investigated as antibacterial agents, especially in comparison with other Gram-negative pathogens [ 63 , 64 , 65 ]. In a recent work, Alves et al reported that the majority of Proteus phages they studied produced clear plaques surrounded by haloes, which is a well-known characteristic of phage depolymerase activity; despite that, the authors were unable to identify the ORFs encoding potential depolymerases in the genomes of the bacteriophages they sequenced [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phages, as well as their derivative enzymes, provide potential means for the development of treatment methods for future phage therapies [ 128 ]. Evidence indicates that enzymes from the isolated Streptococcus and Chlamydia phages can target S. agalactiae and C. trachomatis to impact their growth.…”
Section: Challenges Associated With Application Of Phage Therapy In Bacterial Sexually Transmitted Infectionsmentioning
confidence: 99%